Formation of project management in the executive authorities of the Municipal formation of the city of Kazan? Republic of Tatarstan - Filimonov P. A. (Science, education, society: trends and prospects, 2019)
The archive provides an analysis of the development of project management in public authorities. Based on the information received, the stages of development of the project management in the executive authorities and the most acute areas for solving strategic problems were identified. The possible results of the implementation of project of the Municipal formation of the city of Kazan of the Republic of Tatarstan were considered.
Keywords: проектная деятельность; проект; стратегическое планирование; Республика Татарстан; project; project activity; strategic planning; проектное управление; руководящие документы; город Казань; Republic of Tatarstan; project manager; governing documents; city Kazan